Prevalence of bla VIM, bla IMP and bla KPC Genes among Carbapenem-Resistant Klebsiella pneumoniae (CRKP) Isolated from Kurdistan and Isfahan Hospitals, Iran. - Leila Gheitani; Hossein Fazeli (Research in Molecular Medicine, 2018)
Carbapenem resistance among Klebsiella pneumoniae, is an emerging problem worldwide. One of the main mechanisms of resistance to carbapenems is potential of Klebsiella pneumoniae to produce carbapenemase enzyme. The aim of this study was to determine the frequency of bla VIM, bla IMP and bla KPC genes among Carbapenem-Resistant Klebsiella pneumoniae (CRKP) isolated from Kurdistan and Isfahan hospitals. This study was carried out in Iran on 183 samples from Besat and Alzahra hospitals in 2017. Antibiotic susceptibility tests were performed by Kirby-Bauer disc diffusion. The Modified Hodge Test (MHT) was used to investigate the carbapenemase presence. The β -lactamases genes were detected by PCR method. The highest and the lowest rate of resistance were observed against cefotaxime (98.2%) and gentamicin (43.6%) respectively. Among 183 isolates, 134 (73.2 %) of them were positive in MHT. The prevalence of bla VIM, bla IMP and bla KPC  genes was 4  (2.18%), 1 (0.5%) and 0% respectively. The prevalence of CRKP (Carbapenem-Resistant Klebsiella pneumonia) strains detected in this study is a major concern and the need of infection control process of care measures. Regarding to our findings, these gene has low prevalence in the our country, probably other mechanisms of resistance to Carbapenems , are involved.